How do you solve #x^2 - 6x + 2 = 0# using the quadratic formula?

1 Answer
Mar 10, 2016

Answer:

#x=3+-sqrt7#

Explanation:

#color(blue)(x^2-6x+2=0#

This is a Quadratic equation (in form #ax^2+bx+c#)

Quadratic formula

#color(brown)(x=(-b+-sqrt (b^2-4ac))/(2a)#

Where

#color(red)(a=1,b=-6,c=2#

Substitute the values in the formula

#rarrx=(-(-6)+-sqrt(-6^2-4(1)(2)))/(2(1))#

#rarrx=(6+-sqrt(36-8))/(2)#

#rarrx=(6+-sqrt(28))/2#

#rarrx=(6+-sqrt(4*7))/2#

#rarrx=(6+-2sqrt(7))/2#

#rarrx=(cancel6+-cancel2sqrt(7))/cancel2#

#rArrcolor(green)(x=3+-sqrt7#